Indirect Tax Incidence in Brazil : Assessing the Distributional Effects of Potential Tax Reforms - Lara Ibarra, Gabriel; Rubiao, Rafael Macedo; Fleury, Eduardo (World Bank, Washington, DC, 2021)
Using recent expenditure survey data, this paper investigates the incidence of all indirect taxes in Brazil. It applies a novel approach to estimate the effective tax rate by computing the specific cumulative taxes levied on thousands of items available in the data set. The findings show that for every R$100 of indirect tax revenue, the first and second deciles pay R$2 and R$3, respectively, while the ninth and tenth deciles pay R$16 and R$33, respectively. Meanwhile, indirect taxes represent between 23 and 45 percent of income among the poorest households. Simulations of a value-added tax reform suggest that it could be inequality reducing both horizontally and vertically. A flat value-added tax accompanied by excise taxes on fuel items, alcohol, and tobacco would also lead to lower decreases in expenditures. Households would spend 2.8 percent less on average, with those in the bottom (top) decile spending 7.0 percent (1.5 percent) less.